تأثير الضغوط المهنية على استاذ التربية البدنية والرياضية - قدادرة, شوقي (جامعة الوادي - University of Eloued, 2020)
ان مهنة تدريس مادة التربية البدنية والرياضة تحتاج بشدة إلى قيادة مؤهلة هي أساس لتحقيق الكثير من إمكانياتها، حيث أن أستاذ التربية البدنية والرياضية يعتبر من أبرز أعضاء هيئة التدريس بالمجتمع المدرسي، ولدبه تأثيرا في تشكيل الأخلاق والقيم الرفيعة ويعتمد في ذلك على التوفيق بين ميول التلميذ وإمكانيات المؤسسة التعليمية وقدراته الشخصية في تقديم واجبات تربوية في إطار بدني رياضي يهدف إلى النمو والتكيف. إلا أن استاذ التربية البدنية والرياضية ليس مجرد مجموعة من الخصائص والصفات الحميدة بل هو إنسان وقائد قادر على تلبية الحاجيات الانفعالية من متغيرات عديدة تشكل له ضغط على حالته النفسية، كالحالة المعيشية والمشاكل المهنية. وقد جاءت أهداف الدراسة على سياق واحد وهو معرفة تأثير الضغوط المهنية على استاذ التربية البدنية والرياضية والدور الهام الذي تلعبه التربية البدنية والرياضية في تحقيق أهداف التربية العامة جعلها موضع اهتمام مقارنة مع ما كانت عليه، فأصبح بذلك دور أستاذ التربية البدنية والرياضية مهما وصعبا في نفس الوقت خاصة أمام واقع تملؤه الاضطرابات والصراعات جراء ما يعاني منه المجتمع من مشاكل عدة مست مختلف الميادين، والتي شكلت ضغطا على نفسية الفرد. أما بالنسبة للنتائج فكانت كلها حسب التوقعات الموضوعة من طرف الباحث ،إن معاناة أستاذ التربية البدنية والرياضية من الضغط المهني تؤثر فيه عدة عوامل أو أسباب منها قلة أو انعدام المنشآت الرياضية وعدم توفر الوسائل البيداغوجية بالإضافة إلى العوامل المحيطية و المناخية. The teaching profession of physical education and sport requires strong leadership is the basis for achieving many of its potential, as the professor of physical education and sports is one of the most prominent members of the school community, and his teacher influence in the formation of ethics and high values and depends on the reconciliation between the student's tendencies and possibilities The educational institution and its personal abilities in the provision of educational duties in the framework of physical physical sport aimed at growth and adaptation. However, the professor of physical education and sports is not only a set of characteristics and qualities of good, but is a human being and a leader able to meet the emotional needs of many variables that stress him on his psychological condition, such as living conditions and occupational problems. The objectives of the study were based on one context, namely, the impact of professional pressures on the teacher of physical education and sports, and the important role played by physical education and sports in achieving the objectives of public education, making them a matter of interest compared to what they were. This has made the role of professor of physical education and sports difficult and difficult at the same time Especially in the face of a reality of turmoil and conflict as a result of the various problems facing the society in different fields, which put pressure on the psyche of the individual. As for the results were all according to the expectations of the researcher, the suffering of the professor of physical education and sports from the occupational pressure affected by several factors or reasons, including the lack or lack of sports facilities and the lack of pedagogical methods in addition to peripheral and climatic factors.
مقال
Keywords: الضغوط المهنية ، الاستاذ ، التربية البدنية والرياضية.; Professional pressures, professor, physical education and sports